Cardiovascular-renal protective effect and molecular mechanism of finerenone in type 2 diabetic mellitus - Lv, Ruolin; Xu, Lili; Che, Lin; Liu, Song; Wang, Yangang; Dong, Bingzi (Frontiers in Endocrinology, 2023)
Chronic kidney diseases (CKD) and cardiovascular diseases (CVD) are the main complications in type 2 diabetic mellitus (T2DM), increasing the risk of cardiovascular and all-cause mortality. Current therapeutic strategies that delay the progression of CKD and the development of CVD include angiotensin-converting enzyme inhibitors (ACEI), angiotensin II receptor blockers (ARB), sodium-glucose co-transporter 2 inhibitors (SGLT-2i) and GLP-1 receptor agonists (GLP-1RA). In the progression of CKD and CVD, mineralocorticoid receptor (MR) overactivation leads to inflammation and fibrosis in the heart, kidney and vascular system, making mineralocorticoid receptor antagonists (MRAs) as a promising therapeutic option in T2DM with CKD and CVD. Finerenone is the third generation highly selective non-steroidal MRAs. It significantly reduces the risk of cardiovascular and renal complications. Finerenone also improves the cardiovascular-renal outcomes in T2DM patients with CKD and/or chronic heart failure (CHF). It is safer and more effective than the first- and second-generation MRAs due to its higher selectivity and specificity, resulting in a lower incidence of adverse effects including hyperkalemia, renal insufficiency and androgen-like effects. Finerenone shows potent effect on improving the outcomes of CHF, refractory hypertension, and diabetic nephropathy. Recently studies have shown that finerenone may have potential therapeutic effect on diabetic retinopathy, primary aldosteronism, atrial fibrillation, pulmonary hypertension and so on. In this review, we discuss the characteristics of finerenone, the new third-generation MRA, and compared with the first- and second-generation steroidal MRAs and other nonsteroidal MRAs. We also focus on its safety and efficacy of clinical application on CKD with T2DM patients. We hope to provide new insights for the clinical application and therapeutic prospect.